(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research aims to analyze Ostracization (Muukuu Muruu) as boycotting and Green Card Grabbing System in Seera Ambaa. To conduct this study, the researcher prefers to use a qualitative method as it is appropriate for the analysis, presentation, and interpretation of empirical data. To collect this data from Arsi Oromo elite elders and the head of the council, the researcher prefers purposive and snowballing sampling to select the research sample. To collect data from the informants’ interviews, participant observation, and focus group discussion were selected. Last but not least, to analyze and interpret the ethically collected data he selected the qualitative method. From the analysis and interpretation made, the major findings of this research are: Arsi Oromo Customary law plays a paramount role in controlling and regulating the relationship of the community by enforcing its code of conduct. This is very important for having a secure and peaceful family. Ostracization and a green card-grabbing system is the last and permanent form of punishment which is irreversible by any means once decided by community elders. So, they are very important in controlling and monitoring the action and behavior of a member of society to act or behave against the predetermined laws. The major recommendations are: Arsi Oromo customary law (seera ambaa) plays a significant role in protecting human rights and justice, it is vital if it functioning properly, the role of Arsi Oromo Customary law (seera ambaa) in regulating and controlling socio-economic affairs is paramount. So, it is very important if it is included in the legal documents at regional and national levels, Arsi Oromo Customary Law or Seera Ambaa plays a paramount role in avoiding double jeopardy. So, it is vital to promote it by District Culture and Tourism Office, it is vital to amend AOCL to address the issue of females in democratic and nonpartisanship as affirmative action by Qaalluu up on the request of Arsi Abbaa Gadaa and Siinqee institutions.